Immune Pathology Associated with Altered Actin Cytoskeleton Regulation - Wickramarachchi, Dilki (2010)
The actin cytoskeleton plays a crucial role in in a variety of important cellular processes required for normal immune function, including locomotion, intercellular interactions, endocytosis, cytokinesis, signal transduction and maintenance of cell morphology. Recent studies have uncovered not only many of the components and mechanisms that regulate the cortical actin cytoskeleton, but have also revealed significant immunopathologic consequences associated with genetic alteration of actin cytoskeletal regulatory genes. These advances have provided new insights into the role of cortical actin cytoskeletal regulation in a number of immune cell functions, and have identified cytoskeletal regulatory proteins critical for normal immune system activity and susceptibility to autoimmunity.